2013
DOI: 10.3233/cbm-130307
|View full text |Cite
|
Sign up to set email alerts
|

Identification of low abundance proteins in colorectal cancer tissues

Abstract: The proteins were isolated from the cancerous tissues as either up-regulated or down-regulated proteins as compared to normal tissues and therefore may play important roles in cancer development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The expression of LRRN4 was high in CRC and was correlated with pathological stage and OS status in the TCGA cohort and our cohort. However, a previous study found that LRRN4 was of low abundance in normal colon tissue and that the level of LRRN4 was much lower in CRC tissue, which was detected by coupling hydroxyapatite chromatography and SDS-PAGE followed by mass spectrometry analysis [ 18 ]. In fact, in a few cases, we also found that the expression of LRRN4 is higher in normal tissues than in tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of LRRN4 was high in CRC and was correlated with pathological stage and OS status in the TCGA cohort and our cohort. However, a previous study found that LRRN4 was of low abundance in normal colon tissue and that the level of LRRN4 was much lower in CRC tissue, which was detected by coupling hydroxyapatite chromatography and SDS-PAGE followed by mass spectrometry analysis [ 18 ]. In fact, in a few cases, we also found that the expression of LRRN4 is higher in normal tissues than in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…LRRN4 has been identified as a marker of primary mesothelial cells, while it was found to be either nondetectable or downregulated in mesothelioma [ 17 ]. Although LRRN4 was not highly expressed in normal colon tissue, the level of LRRN4 was much lower in CRC tissue, as detected by the coupling methods of hydroxyapatite chromatography and SDS–PAGE followed by mass spectrometry analysis [ 18 ]. However, the clinical significance of LRRN4 remains to be clarified by investigation in a larger sample.…”
Section: Introductionmentioning
confidence: 99%